THE STRATEGY OF KIE VASECTOMY/MOP METHOD IN ATTEMPT TO INCREASE KB PRIA LESTARI ACCEPTOR (Case Analysis in Badung District and Surabaya City) - Panji Dwi Ashrianto; Basuki Basuki (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2018)
reproduction by concerning about the rights of reproduction and gender equality. One of the attempt or effort is men participation in KB whether it is by condor or vasectomy. The socialization of MOP Method is not easy. Many contradictions come from both man and wife. The man’s side are hard to accept because afraid of erection dysfunction (not manly enough). While the wife’s side are afraid if their husband cheating. Government Program (BKKBN) is formulating the Strategy of KIE and the counseling service for vasectomy. The interesting phenomenon is the achievement from the government of Surabaya city on 2013 MGDs Award on the health of mother and child category with excellent program “Pioneering and Empowerment the Group of Vasectomy Participants”. In Badung District one midwife, Nyoman Rai Sudani won the “Bidan Teladan Nasional” (National Exemplary Midwife) competition in 2011 because of her achievement in increasing and forging the vasectomy acceptor. The aim of this research is synthesizing the strategy of KIE vasectomy in Surabaya City and Badung district. Result of the research shows, the usage of face-to-face communication is effective for vasectomy method acceptance. However, on its development, the officials think that this method cannot create public opinion. Therefore, there is activity called “gerebegpasar& terminal”. Together, (officials, health cadre and Man KB Community) introduce vasectomy to the crowd in that place. The term vasectomy changed to “KB Lanang”. Enthusiasms from the community in that place to discuss and continued to participate in vasectomy need to appreciate. The achievement of this method then adopted by government by improving with service infrastructure such as car and doctor. They who interested in this program could directly do vasectomy. In this case testimony is important factor on opinion creation and the behavior of vasectomy participant candidate.